Critical Role of Rate of Seed Drying in Maintaining the Seed Viability Potential of Recalcitrant Seeds of Ligustrum perrottetii - E KANTHAIYA AADHAVAN; R UMARANI (Seed Research, 2026)
Changes in physiological potential of the recalcitrant seeds of Ligustrum perrottetii, were examined after subjecting the seeds to differential rate of drying by exposing the fruits to variable relative humidity and silica gel ratios. Periodic observations on fruit and seed characteristics and topographical tetrazolium staining was conducted to observe the pattern of staining in the regions of embryonic axis and cotyledon. The experiments revealed that highest rate of drying caused by highest seed : silica gel ratio and lowest RH had resulted in higher electrical conductivity (dSm-1) and vice versa. The higher rate of drying, had caused maximum damage to membrane integrity as revealed by high electrical conductivity of seeds with corresponding decrease in seed viability potential. Detailed observation of staining patterns in seeds stored in conditions causing differential rates of drying envisaged that embryonic axis tissues were more sensitive to drying compared to the cotyledons. Among the three temperatures viz., ambient (Max 30.9 oC, Min 18.2 oC; 65% RH), 10oC (41% RH) and – 3.3oC (27% RH), the rate of drying was more gradual in 10oC (41% RH), and it resulted in higher viability potential (20 percent of fully stained seeds) even after four weeks of storage. It is phenomenal be-cause, within four weeks of storage, all the seeds had become nonviable, in all other storage conditions. In future, recalcitrant seed storage should be experimented in a constant temperature of 10oC at levels of relative humidity still higher than 41%, so as to further reduce the rate of drying which is crucial to reduce mechanical damage and metabolism induced damage which are characteristic of recalcitrant seed which are shed from the tree at very high seed moisture content.